A pilot study of co-produced autism training for police custody staff: evaluating the impact on perceived knowledge change and behaviour intentions. Issue 3 (15th March 2022) - Holloway, Chloe; Munro, Nell; Cossburn, Kleio; Ropar, Danielle
Abstract : Purpose: Autistic people have reported particularly negative experiences in police custody, which can lead to significant long-term personal and legal consequences. Research has suggested providing autism training to police forces would help improve the support of autistic people, but there is a distinct lack of appropriate autism training available. An evidence-based autism training package specifically tailored to the roles of custody staff was co-produced by autistic people, academics and police staff to address this. A pilot study was conducted to further understand its value in terms of perceived changes in knowledge and future behaviour intentions. Design/methodology/approach: A total of 18 sessions were held across five police forces in England attended by police staff working in custody ( n  = 142). The sessions were delivered in person using a presentation and video replicating the experiences of autistic people during the custody process. Attendees completed a survey rating their perceived changes in knowledge of autism after the session and described changes they planned to make in their practice to support autistic people. Findings: The majority of police custody officers rated the training highly on its content, delivery and informativeness about autism. Participants also reported a change in perceived knowledge about autism, with those who reported having the least amount of knowledge prior to training indicating the greatest change. Responses about intended changes to future behaviour and practice showed a clear indication of specific understanding about autism and strategies to support autistic individuals in custody. Originality/value: This is the first study to outline, assess and evaluate the impact of the first evidence-based and co-produced autism training package specifically designed for custody staff on perceived knowledge and intended behaviour.